Greening agriculture as a response to climate change: a case study from China over 2000–2021 - Niangjijia Nyangchak; Motso Yang (Frontiers in Sustainable Food Systems)
Green agriculture is critical for tackling climate change by ensuring carbon neutrality and food security. This article assesses green agriculture as a response to climate change through green efficiency and the underlying mechanisms of green agricultural development in China’s Qinghai Province from 2000 to 2021. It employs a non-radial and non-oriented DEA model, super Slacks-Based Measure, to gage green efficiency. The Logarithmic Mean Divisia Index decomposition model and the Tapio decoupling model are utilized to further analyze the influencing factors and trends in greening the agriculture. Field research has been conducted to gain a holistic understanding of the intricate factors steering sustainable agriculture. The study reveals that Qinghai’s journey in greening agriculture is marked by distinct stages: stabilization (2000–2008), deterioration (2009–2016), recovery (2017–2019), and efficient stage (2020–2021). Notably, shifts in policies and input structures have influenced the green efficiency in agricultural production. The province has largely retained strong decoupling since 2012, indicating the effectiveness of sustainable practices in mitigating the detrimental impacts of intensive farming. The study also identifies economic growth as the primary factor negatively impacting green efficiency, followed by energy intensity, carbon intensity, and population scale. Finally, the study outlines policy insights for greening agriculture.